Polysemy, diachrony, and the circle of cognition - Fortescue, Michael D. 1946- (Brill's studies in language, cognition and culture, 2021)
"Verbs of mental states or activity constitute a subject of considerable interest to both Cognitive Linguistics and Linguistic Typology. They promise to open a window on the invisible workings of the mind, while at the same time displaying a wide variety of historical sources across languages. In this book Michael Fortescue presents an innovative approach to the semantics and diachronic source of cognitive verbs across a representative array of the world's languages. The relationship among the cognitive verbs of individual languages is essentially one of metonymy, and the book investigates in detail the specific metonymic relationships involved, as revealed largely by the polysemous spread of word meanings. The data is projected against a circular 'map' of interrelated cognitive categories"--